99TCm-HMPAO SPECT studies in traumatic intracerebral haematoma. Issue 1 (January 1991) - Choksey, M S; Costa, D C; Iannotti, F; Ell, P J; Crockard, H A
Abstract : Traumatic intracerebral haematomas are a common neurosurgical emergency. Their management, particularly the role of surgical removal, is controversial. Deterioration often occurs late, and is unpredictable. Eight patients with traumatic intracerebral haematomas were admitted to the neurosurgical unit to monitor their clinical state. All were studied within 48 hours of admission with single photon emission computerised tomography (SPECT), using the recently introduced radionuclide 99Technetiumm-Hexamethyl propylene amine oxime (99Tcm-HMPAO). At the time of the SPECT study, all the patients had been clinically stable. Three patients remained so; in the other five, the conscious level deteriorated, necessitating craniotomy and evacuation of the haematoma. In all the patients, the SPECT studies demonstrated perfusion defects that corresponded to the location of the haematoma, as demonstrated by computerised tomography (CT). However, in the five patients who subsequently deteriorated, the perfusion defects seen on the SPECT scan appeared larger than the haematoma, as seen on the CT scan. In addition, there was widespread poor retention of 99Tcm-HMPAO in the ipsilateral hemisphere. These differences were quantifiable. Interestingly, these differences were present at a time when the patients were clinically stable, before their deterioration. It is concluded that SPECT studies with 99Tcm-HMPAO are of possible use as predictors of late deterioration in the management of traumatic intracerebral haematomas.